Collagen fibers as biomass templates constructed multifunctional polyvinyl alcohol composite films for biocompatible wearable e-skins - Wang Ya-nan; Niku Guge; Chen Hao; Wang Yujia (Science and Engineering of Composite Materials)
Multifunctional characteristics are of significance for development of bionic skin materials. Herein, we report the collagen fibers (CFs) as biomass templates constructed multifunctional polyvinyl alcohol composite films (PCBPP) that integrate the diverse properties including the good thermal stability, water resistance, self-healing ability, adhesiveness, benign biocompatibility, and sensitive electrical signal response within a single structure, realize much more favorable functionalities in mimicking natural skin. The CFs as biomass template well immobilize and stabilize the polypyrrole (PPy) nanoparticles, which simultaneously improves the dispersity of PPy and enhances its conductivity. More importantly, due to the CFs constructed conductive paths and micro- and nano-sensing structure, the PCBPP prepared e-skin exhibits the GF value of 0.366 in the strain range of 10–40% and is able to distinguish different strain intensities and monitor the movements of the human body, including wrist bending, elbow bending, and swallowing. The self-healed PCBPP prepared e-skin exhibited the recoverable sensitivity. Our investigation provided a new prospect for designing CFs as conductive network packed multifunctional composite film and the as-prepared PCBPP exhibits great potential for versatile applications in various wearable devices and in the field of artificial intelligence.